Smart curtain / Muhammad Syafiq Shamsul Baharin & Mohd Syafiq Izwan Radzi - Shamsul Baharin, Muhammad Syafiq; Radzi, Mohd Syafiq Izwan (2015)
This curtain controller uses an Arduino UNO as the brain to control the opening of curtain veils, thus enabling the control of light intensity in the room. It features both automatic mode and manual override mode. In the automatic mode, we can set the preferred intensity level in the room using a pot and the control system will adjust the veils suitably to maintain the user set intensity level always. As the name indicates, in the manual override mode the user is free to choose any opening of the veils. The working of the circuit is fairly simple. When the mode switch is open, the system is in automatic mode. In this mode, the analog voltage at pin at Arduino which is set by the potentiometer is compared with the analog voltage output of the light dependent. If the output of the light dependent resistor is lower than the potentiometer, this means that the light intensity inside the room is less than the value required. So the veil should open up till these two values matches. Similar is the case when the output of LDR is higher than pot, thus causing the veil to close till the equilibrium reaches. When the mode switch is in closed position the system is in manual override. Now the control algorithm is disabled and the user can set the veil to any position of his/her choice. The mode will be indicated by the liquid crystal display (LCD) connected to the microcontroller for easier reference to use.